On the variational statement of one boundary-value problem with free interface - Timokha, A. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 532.595With the help of Clebsch's potentials, we propose a Bateman–Luke-type variational principle  for a boundary-value problem with a free (unknown) interface between two ideal compressible barotropic fluids (liquid and gas)  admitting rotational flows.